2020
DOI: 10.1101/2020.02.27.968792
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Distinct organization of two cortico-cortical feedback pathways

Abstract: Neocortical feedback is critical for processes like attention, prediction, and learning. A mechanistic understanding of its function requires deciphering its cell-type wiring logic. Recent studies revealed a disinhibitory circuit between motor and sensory areas in mice, where feedback preferentially targets vasointestinal peptide-expressing interneurons, in addition to pyramidal cells. It is unknown whether this circuit motif is a general cortico-cortical feedback organizing principle. Combining multiple simul… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 78 publications
(98 reference statements)
1
7
0
Order By: Relevance
“…We predict that systems with more feedback noise (e.g. SOM versus VIP) would have less predictive suppression, as observed experimentally [49].…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…We predict that systems with more feedback noise (e.g. SOM versus VIP) would have less predictive suppression, as observed experimentally [49].…”
Section: Discussionsupporting
confidence: 63%
“…These architectures have different microcircuits with distinct feedforward and feedback projection neurons. For example, feedback in different visual and motor cortical systems tends to target different inhibitory cells [49] which have different noise levels [50,51]. We predict that systems with more feedback noise (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the direct FB-to-FF connections we have found here could underlie the facilitatory effects of FB, but direct or indirect contacts with inhibitory neurons are necessary to mediate the FB suppressive effects found experimentally and postulated by predictive coding. Indeed, direct FB contacts with inhibitory neurons have been demonstrated in both mouse [64][65][66] and primate 67 visual cortex. Therefore, the monosynaptic FB-FF contacts we have found in this study represent just one of several motifs of FB connectivity in primate cortex.…”
Section: Figure 9 About Herementioning
confidence: 99%
“…3C). Furthermore, anatomical data indicate that synapses from HVAs terminate on L1 and L2/3 apical dendrites of pyramidal cells (whose cell bodies reside in L2/3 or L5) (Glickfeld and Olsen, 2017; Marques et al, 2018; Hartmann et al, 2019; Keller et al, 2020; Shen et al, 2020). Together, these observations suggest that the sustained L2/3 sink and L4 source might, in part, be induced by feedback from higher visual areas (HVA), where the sink is generated from the input to the apical tufts in L1 and L2/3, and the source may be the return currents of this input.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have shown that feedback from higher visual areas can exert a strong influence on the magnitude of LFP during evoked responses (Hartmann et al, 2019). To investigate whether such cortico-cortical influence can contribute to the sinks and sources of the canonical CSD pattern, we added feedback consisting of experimentally recorded spikes from the higher cortical visual area LM (Siegle et al, 2021) impinging on synapses placed onto V1 neurons in our model, using anatomical data (Glickfeld and Olsen, 2017; Marques et al, 2018; Hartmann et al, 2019; Keller et al, 2020; Shen et al, 2020). We found that the feedback can play a significant role in shaping the sustained sinks and sources (Fig.…”
Section: Discussionmentioning
confidence: 99%